Oral Hygiene Practices among Patients from Different Socioeconomic Status: An Observational Study - Tyagi, Dr. Shruti; Prasad Indra B, Dr. Niranjana; Gokkulakrishnan, Dr. S.; Vashishtha, Dr. Bhart (International Research in Medical and Health Sciences, 2025)
Aim: To assess the differences in oral hygiene practices among patients from different socioeconomic statuses visiting the outpatient department of the Institute Of Dental Sciences, Bareilly. Material and Method: An observational study was conducted in the month of May 2024 to assess the effect of SES on oral hygiene habits. The questionnaire included questions related to the demographic profile and assessment of the oral hygiene habits of the study population. The SES of the population was assessed using modifyied kuppuswamy scale which is based on per capita income per month, educational status, and occupational status of the study population. Result: A total of 128 individuals were included out of which the mean age of the study population was 41-50 years with an average percentage of about 28.9%.Out of all 60.2% of male and 39.8% of female population were included. The study population comprised 14.8% of patients belonging to the lower class, 66.4% belonging to the upper lower class, 16.4% belonging to a lower middle class, and 2.3% patients belonging to the upper middle class. Conclusion: The oral hygiene practices among the patients belonging to the upper-lower class were found to be satisfactory when compared to the lower and middle-class populations. The percentage of people using oral hygiene aids other than toothbrush and toothpaste was very less. Therefore, education and motivation among the people about the oral hygiene maintenance along with proper selection and use of the various oral hygiene aids is necessary in order to maintain aqeduate oral health.